2010
DOI: 10.1016/j.archoralbio.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nifedipine on gingival enlargement and periodontal breakdown in ligature-induced periodontitis in rats

Abstract: Nifedipine itself did not lead to gingival enlargement in rats. In the presence of biofilm accumulation, nifedipine yielded greater gingival enlargement and periodontal inflammation, but it did not increase periodontal destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…It might be due to different size of sample or different related prescribed doses. On the other hand, we emphasize that although amlodipine shows great GE prevalence when used in combination with CsA, this combination displays lower GE prevalence and severity than that revealed in CsA-nifedipine combination (2, 6). In addition, other risk factors were not significantly effective on periodontal lesions in the current study.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…It might be due to different size of sample or different related prescribed doses. On the other hand, we emphasize that although amlodipine shows great GE prevalence when used in combination with CsA, this combination displays lower GE prevalence and severity than that revealed in CsA-nifedipine combination (2, 6). In addition, other risk factors were not significantly effective on periodontal lesions in the current study.…”
Section: Discussionmentioning
confidence: 60%
“…Drug induced GE is a clinical condition characterized by an increase in the size of gingival tissues leading to an alteration in gingival contour (6). It could be the side effect of several drugs such as anticonvulsants, immunosuppressive agents, and calcium channel blockers (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Según diversas investigaciones 18,19,20,21 , la inflamación gingival provocada por el acumulo de placa bacteriana es un factor muy importante para la aparición y severidad del agrandamiento gingival. En nuestro estudio, al realizar el llenado del periodontograma pudimos observar la presencia o ausencia de inflamación, pero no fue posible correlacionar estas variables con seguridad ya que se realizó de forma transversal.…”
Section: Discussionunclassified
“…The exact mechanism of induction is unclear, although several studies suggest that resident fibroblasts produce more collagen and other extracellular matrix molecules than normal [2]. More recently, studies have shown that the epithelial thickness encountered in gingival overgrowth could be associated with an increase in the mitotic activity of the epithelium, as measured by the expression of proliferation markers [3]; in rats, nifedipine itself did not lead to gingival enlargement, but in the presence of biofilm accumulation, nifedipine yielded greater gingival enlargement and periodontal inflammation, however there was no increase in periodontal destruction [4].…”
Section: Introductionmentioning
confidence: 99%